Basic perspective drawing : a visual approach - Montague, John, 1944- (John Wiley & Sons, 2010)
The best-selling guide ... now completely updated to include online tutorials! Basic Perspective Drawing introduces students, both those in formal design courses and self-learners, to the basic principles and techniques of perspective drawing. Clear and accessible illustrations show how to construct perspective views one step at a time. The new, streamlined Sixth Edition contains must-have content for students and instructors in art and design, architecture, and interior design programs. Updated illustrations reflect the most current drawing styles and examples while supplementary tutorial video.